2019
DOI: 10.2298/fil1914665b
|View full text |Cite
|
Sign up to set email alerts
|

A remark on asymptotic regularity and fixed point property

Abstract: In this paper, we show that orbital continuity of a pair of non-commuting mappings of a complete metric space is equivalent to fixed point property under the Proinov type condition. Furthermore, we establish a situation in which orbital continuity turns out to be a necessary and sufficient condition for the existence of a common fixed point of a pair of mappings yet the mappings are not necessarily continuous at the common fixed point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…4. The technique of proof used in the present paper, essentially based on the concepts of graphic contraction and approximate fixed point sequence, could also be nontrivially applied to other classes of self and nonself single-valued mappings in the literature on metric fixed point theory, see [5,[7][8][9][10][11][12]14,20,23,28,31,36,38,39,42,44,46,50,60,61,63] etc. 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4. The technique of proof used in the present paper, essentially based on the concepts of graphic contraction and approximate fixed point sequence, could also be nontrivially applied to other classes of self and nonself single-valued mappings in the literature on metric fixed point theory, see [5,[7][8][9][10][11][12]14,20,23,28,31,36,38,39,42,44,46,50,60,61,63] etc. 5.…”
Section: Discussionmentioning
confidence: 99%
“…5. There exists another important technique for proving metric fixed point theorems which is based on the property of asymptotic regularity of the mappings, see [14,[29][30][31], and which is naturally closely related but independent to the technique emphasized in the current paper, in view of Theorem 3.1 in [13], which shows that, for a nonempty set X and a mapping T : X → X , the following statements are equivalent: (a) there exists a complete metric on X with respect to which T is a continuous graphic contraction; (b) Fi x (T ) = ∅ and there exists a metric on X with respect to which T is asymptotically regular.…”
Section: Discussionmentioning
confidence: 99%
“…In the case F = {x * }, i.e., when is a Picard operator, the problem was studied in [127] and [21], see also [24] and [80].…”
Section: Problemmentioning
confidence: 99%
“…Moreover, it has been shown that a lot of metric fixed point theorems can be extended to b-metric spaces [11,58], although b-metric, in the general case, is not continuous, lim [6,21] for further details). The notion of b-metric spaces were introduced to reach the generalization of some known fixed point theorems for single valued mappings and correspondences [9,10,15,16].…”
Section: Introductionmentioning
confidence: 99%